Market Mechanisms and Electricity Export Pricing: A Comparative Study of Wholesale and Bilateral Trade Models - Baayeh, Kenneth; Oyelakin, Idris Oyewale; Aubynn, Anthony; Azamelah, Emmanuel Yaovi; Enimil, Doris; Singh, Ajit Kumar (International Journal of Energy Economics and Policy, 2025)
The price of electricity exports affects global energy markets because of the increase of grid interconnections and decarbonization requirement. The model of wholesale (PJM Interconnection), bilateral (Iran cross-border trade), and hybrid (EU market coupling) will be compared in the study to determine the efficiency of pricing, market transparency, integrating renewables and cross-border trade in totality. The mixed-methodology approach is the combination of the qualitative analysis of policy and the quantitative indicators which are based on both primary and secondary sources. Although the model of PJM (wholesale strategy) ensures competent pricing, it lacks integration of renewable and is highly volatile. Bilateral model of Iran offers non-transparent non-renewable non-flexible pricing. Despite the existence of legislative fragmentation, the hybrid approach of the EU has reached equal pricing, reduced volatility, and high integration of renewable. The hybrid strategies allow maximising the export price and sustainability under the support of joint governance, institutional reform and transition-oriented policies. The suggested policies include the dynamic pricing mechanisms of PJM, transparent reporting of the contracts of Iran and the EU-style regional integration of emerging markets. Future research may consider blockchain-based trade to enhance the transparency and carbon pricing to enhance renewable shares as scalable solutions to world energy transitions, while addressing environmental and economic challenges.